Variation in antibody titers determined by Abbott and Roche Elecsys SARS-CoV-2 assays in vaccinated healthcare workers - Miku Nakai; Daisuke Yokoyama; Tomoaki Sato; Ryohei Sato; Chiari Kojima; Tatsuo Shimosawa (Heliyon, 2023)
SARS-CoV-2-specific antibody measurement is important for evaluating COVID-19 vaccine efficacy. We quantified and compared anti-spike (S) antibodies using different commercial immunoassays. We tested serum samples from 70 SARS-CoV-2-naive health care workers 2 weeks after vaccination with a single dose of BNT162b2, 2 and 4 weeks, and 3 months after the second dose of BNT162b2. The following quantitative assays were used: Roche Elecsys Anti-SARS-CoV-2 S (Roche-S), Abbott SARS-CoV-2 IgG II Quant [Abbott-IgG(S)], and Abbott SARS-CoV-2 IgM (Abbott-IgM). All samples tested positive for Roche-S and Abbott-IgG antibodies after the second dose, with 83.6% Abbott-IgM positive rate. Roche-S and Abbott-IgG(S) correlated significantly in all samples (r = 0.920, p < 0.0001), and the Roche-S and Abbott-IgG(S) assay showed a strong correlation with each other at each time point after vaccination. Roche-S and Abbott-IgG(S) antibody titers were correlated with age; their rate of decline was age-dependent in males but not in females. Abbott-IgG(S) antibody titers decreased from 2 weeks after the second dose. Roche-S antibody titers peaked 2 weeks after the second dose in 76.2% of the participants; the titers recovered 3 months post-vaccination after declining at week 4 in 40.7% of the participants. The concordance between Roche-S and Abbott-IgG(S) antibody titers over time was 47.5%. Most participants presented significantly high Roche-S and Abbott-IgG(S) antibody titers after immunization. Some measurements were inconsistent with titer changes between these assays, possibly because of differences in the immunoglobulin-specificity of the kits.